JEDNOSTKA 731 W LITERATURZE POLSKIEJ - Morawiec, Arkadiusz (Prace Polonistyczne, 2020)
The article examines Unit 731, a secret research unit of the Imperial Japanese Army which implemented the programme of the development and production of chemical and biological weapons that was initiated in the 1930s by general Shirō Ishii, as a motif in Polish literature. Unit 731 and the crimes they committed were first openly discussed at the turn of the 1990s, initially in China, South Korea, and Japan, and then in Western countries. This has found some reflection in popular culture, in few literary works, films, songs, RPGs, and comic books (e.g. Ken Liu’s short story The Man who Ended History, Tun Fei Mou’s film Hei tai yang 731, Bruce Dickinson’s song Breeding House, and Paul-Yanic Laquerre, Pastor, and Yang Song’s comic Maruta 454). Surprisingly, Polish literature abounds in early, even pioneering, texts that use the motif of Unit 731. This can be explained by two main reasons. First of all, the publication of Proces japońskich przestępcow wojennych. Materiały rozprawy sądowej w Chabarowsku przeciwko byłym wojskowym japońskiej armii oskarżonym o przygotowanie i użycie broni bakteriologicznej (Materials on the Trial of Former Servicemen of the Japanese Army Charged with Manufacturing and Employing Bacteriological Weapons) in 1951 (a year after the publication of the Russian original). Secondly, the Korean War (1950–1953) or, to be more precise, the communist propaganda that accused the Americans of using the biological weapons co-created by the Japanese war criminals who in 1945 were granted immunity by the American government. Written in the 1950s, the majority of Polish texts that use the motif of Unit 731 are examples of politically-engaged literature of little artistic merit (e.g. Marian L. Bielicki’s Bakteria 0,78, Wanda Melcer’s Statek 1092). Of all of these works, the one that seems most artistically and intellectually sophisticated is Igor Newerly’s Leśne Morze (1960) which critically approaches all ideologies. What may be considered as a Polish literary phenomenon in its own right is the 2011 novel that rescues Unit 731 from many years of oblivion – Marcin Welnicki’s sensational Testament Damoklesa, which shows more affinity to the recent developments in the world’s literature of the last decades than to the earlier Polish literary works. It presents the crimes committed by the Japanese scientists more for a thrilling effect than as a form of political propaganda. Apart from that, similarly to the majority of foreign works, it does not offer any in-depth reflection on history, collective memory, or ethics.